Estrutura genética, divergência morfológica e investimento reprodutivo de Cattleya liliputana (Orchidaceae:Laeliinae), endêmica do Quadrilátero Ferrífero, Minas Gerais, Brasil - Bruno Pereira Leles (2013)
Knowledge of the role of landscapes in shaping genetic connectivity and divergence is essential for understanding patterns of biogeography and diversity. This is particularly relevant for the highly heterogeneous Iron Quadrangle region, a major biodiversity hotspot in eastern South America highlands. Nuclear microsatellites were used to assess the landscape genetics, estimate genetic diversity and explore genetic relationships withmorphological variability and reproductive strategies for seven natural populations of Cattleya liliputana (Orchidaceae). Spatial Bayesian clustering suggested genetic structuring in accordance with pre-established natural populations. Monmonier´s maximum difference algorithm and Bayesian analysis on STRUCTURE identified anmajor discontinuity between Serra do Caraça and Rio das Velhas valley. Populationbased analyses revealed moderate genetic structuring (FST = 0.138, p<0.001) and high genetic diversity and inbreeding (He = 0.733±0.03; Fis = 0.308±0.04). Interpopulation relationships and Mantel tests supported a biogeographical pattern to the distribution of the genetic and morphological variability. We found significant correlation for genetic and morphological diversity among populations. Populations from of the two main genetic and morphological groups also exhibited different investment in the production of flowers. Two distinct groupings were identified within C. liliputana. Each comprises an evolutionarily significant unit, warranting conservation considerations. The currentstudy illustrates that landscape discontinuity drives genetic structuring, morphological divergence and reproductive trade-offs. Isolation over time may lead to morphological changes that can limit reproduction between populations of C. liliputana. These processes in conjunction to high landscape heterogeneity can be an important driver of Cattleya sect. Parviflorae species diversification.